Comparing the molecular and global rheology of a fluid under high pressures - Dench,J; di,Mare L; Morgan,N; Wong,J (Physical Chemistry Chemical Physics, 2018)
The viscosity of liquids is a strong function of pressure. While viscosity is relatively easy to measure at low pressure, high-pressure rheology presents significant experimental challenges. As a result, rheological models are often used to extrapolate viscosity from low pressure measurements to higher pressures. Techniques to obtain data over a wide range of pressures and shear rates, as well as understanding the validity and limitations of methods to fill the gaps in the available data, are therefore of crucial practical and theoretical importance. This work examines the viscosity of polyalphaolefin (PAO) by combining average global area averaged measurements at high pressure and local molecular viscosity measurements at moderate pressures. Viscosities spanning five orders of magnitude are examined at pressures up to 720 MPa. High pressure results were obtained with friction measurements where the fluid is sheared between two surfaces in a loaded point contact. The local molecular microviscosity at medium and low pressures was measured by applying a technique based on fluorescence anisotropy, which probes the rotational motion of dye molecules in a nanoscale film under shear. Both sets of measurements are taken in the same configuration, an elastohydrodynamic (EHD) contact. This is the first set of quantitative local viscosity measurements that have been verified against both friction and high pressure rheometry measurements. Commonly used rheological models were compared to experimental results. Our work shows that fluorescence anisotropy and friction measurements can be used to determine the viscosity of liquids over a wide range of conditions from a single experimental setup. The results obtained match results from low- and high-pressure rheometry for PAO. The importance of correcting friction data for pressure non-uniformity, temperature and shear thinning is also highlighted.